Estudo químico e avaliação de atividades biológicas da espécie vegetal Mabea fistulifera Mart. (Euphorbiaceae) - Coqueiro, Aline (2006)
In the preset work we reported the chemical and biological evaluation, such as toxicity against Artemia salina, antibacterial, atifungal, molluscicidal, antioxidant and anti-inflammatory activities of Mabea fiistulifera Mart. The plant material was divided in: leaves, stem, floral stalks, peels, seeds peels and is and each one was submitted to different exactions using different solvents and were submitted to biological assays, however only the extracts hexane, ethanolic, dicioromethane and ethanoiic on seeds peels were chemicaily study. The fractionation of the hexane extract with different solvents using chromatographic techniques resulted on the isolation of two mixture of long chain hidrocarbon and of the mixtur of [ß-sitosterol and stigmasterol steroids. The flavanons: naringenin 7-O-[ ß -(3",6"-di-p-coumaroyl)glucoside (2), naringenin 7-O-ß-(3"-p-coumaroyl)glucoside (3), naringenin 7-O-ß-(6"-p-coumaroyl)giucoside (4) and naringenin 7-O-ß-giucoside and of the triterpene mixture of α and ß -amirine was isolated of seeds peels. All the ethanoiic extracts and dicloromethane and buthanol fractions were toxic against Artemia salina being ethanolic peels extract the most active with an IC50 = 4,75 μg/mL. For the antibacterial and antifungal evaluation some extracts gave a moderated activity for S. aureus, B. subtilis, C. parapsilosis and C. tropicalis. None of the extracts were active Gran-negative E. coli and P. aeruginosa or even for the yeast C. albicans. For the mollucicidal evaluation none of the extracts were active. For the antioxidant assay the ethl acetate fraction most active with a IC50 = 48.17 μg/mL. For the antiinflamatory evaluation only the floral stalks ethanolic extract suggesting a possible antiinflamatory active.